Military personnel’s satisfaction with antiretroviral services in Namibia: A cross-sectional study - Nestor P.N. Tomas; Nabot P. Kandjimi (Journal of Public Health in Africa)
Background: Patient satisfaction is an indicator of healthcare quality and may affect treatment adherence. It is particularly relevant for military personnel living with human immunodeficiency virus (HIV) because of their increased risks to deployment. However, this phenomenon remains understudied.